The contemporary history of drug-based organised crime in Scotland - McLean, Robert; Holligan, Chris; Pugh, Michael (Emerald advances in historical criminology., 2024)
For nearly twenty years, Glasgow has been coined Europe's murder capital, and identified as having the continent's highest drug harms. The Contemporary History of Drug-Based Organised Crime in Scotland examines converging multiple complexities that contributed to Scotland's criminal modus operandi concentrating on drug-based organised crime. Glasgow is the most populous city in Scotland. The region is likewise responsible for a disproportionate number of the country's crimes. Police Scotland's serious organised crime unit has identified as much as 70% of the country's organised criminal activity to occur within or have ties to the region. A significant amount of these crimes is both directly and indirectly related to the illegal supply of drugs. Numerous law enforcement and political and public responses have been undertaken to reduce violence, organised crime, and drug harms in Scotland. Drawing on key case studies, McLean, Holligan and Pugh shed light on the historical factors that contributed to the embedding of violence, gangs, and drugs into the social fabric of the region. The Contemporary History of Drug-Based Organised Crime in Scotland provides insight into the development of drug based organised crime in the region, and how this process has subsequently shaped the wider criminal landscape of Scotland.